Kinetics, modelling and optimization of Shea butter transesterification via clay doped ionic liquid catalyst - Nwosu-Obieogu Kenechi; Ude Callistus Nonso; Onukwuli Dominic Okechukwu; Ezeugo Joseph (South African Journal of Chemical Engineering)
Developing a cost effective and sustainable fuel from inedible oils and enhancing transesterification process via heterogeneous catalyst with high selectivity prompted this research. The study focuses on evaluating the kinetics, modelling, and optimization of shea butter biodiesel using a clay-doped ionic liquid catalyst. The catalyst employed in this study offers higher selectivity during transesterification process and high biodiesel yield. The parameters considered were temperature, time, agitation speed, catalyst concentration and methanol/oil ratio, while biodiesel yield was considered the response. A novel heterogeneous clay doped ionic liquid heterogeneous catalyst for biodiesel synthesis from shea butter was generated by doping the clay with ionic liquid at a ratio of 2:1 after four hours of calcination at 600 °C. Scanning Electron Micrograph (SEM), X-ray diffraction (XRD), Braut Emmet Teller (BET), Fourier transform infrared spectroscopy (FT-IR), and X-ray fluorescence (XRF) were used to evaluate the catalyst's processability. Tranesterification of the shea butter with methanol was carried out to produce biodiesel and glycerol via a clay doped ionic liquid catalyst. Increase in the process parameters significantly affected the yield, with the highest yield of 89.45 % obtained at an agitation of 300rpm while other parameters were kept constant. After optimisation using response surface methodology (RSM), the second-order polynomial model was shown in the ANOVA with R2 values of 0.9952, Adj R2 (0.9862), and Pred R2 (0.8719), demonstrating model acceptability. The maximum biodiesel yield (97.89 %) was obtained with 2wt. % catalyst, 6 mol/mol methanol/oil ratio, 2.5 h, 61.4 °C, and 400rpm agitation. ANFIS predicted biodiesel yield more accurately than ANN (R2 = 0.999, MSE = 0.11167), with the lowest MSE (R2 = 0.99, MSE = 0.00031). Under optimal conditions, this study employed a kinetic model based on two elementary chemical processes: Eley-Rideal (ER) and Langmuir-Hinshelwood-Hougen-Watson (LHHW). The LHHW model accurately described clay doped ionic liquid catalyst experimental data at 60 °C, with favourable parameters, an R2 value of 0.9992, and a variance of 3.07E-10. The surface reaction linking adsorbed triglyceride and alcohol dictated the rate-determining step (RDS). Temperature increased the rate, indicating an endothermic process. The reaction's activation energy and frequency factor were 75.10 kJ/mol and 2.825E-11 h−1, respectively. Shea butter biodiesel met the D6751 criterion. Nevertheless, the information obtained showed that clay doped ionic liquid catalysts performed effectively in the shea butter biodiesel transesterification process, hence the need to search for more renewable underutilized biomass for catalyst synthesis.